Pulsed radiofrequency treatment for the management of trigeminal neuropathic pain following tooth extraction: A case report - Mohammed Hassan; Conor Gormley; Paul Murphy (Saudi Journal of Anaesthesia)
Post-traumatic trigeminal neuropathic pain is one of the rare complications that could follow orofacial procedures such as dental extraction. The incidence of this type of pain following craniofacial trauma ranges between 3% and 13% depending on the type of surgery. The inferior alveolar and lingual nerves are commonly affected following molar tooth extraction. Pain usually differs from one patient to another concerning intensity and distribution. Pulsed radiofrequency treatment is one of the most widely used techniques in chronic pain management. It focuses on generating heat using radiofrequency waves at higher voltages than conventional radiofrequency while keeping tissue temperature below the neuro-destructive range. This report aims to highlight the benefit of using trigeminal ganglion pulsed radiofrequency to manage neuropathic pain following molar extraction.